Clans, Guilds, and Markets: Apprenticeship Institutions and Growth in the Pre-Industrial Economy - David de la Croix; Matthias Doepke; Joel Mokyr (Institute for the Study of Labor (IZA), 2016)
In the centuries leading up to the Industrial Revolution, Western Europe gradually pulled ahead of other world regions in terms of technological creativity, population growth, and income per capita. We argue that superior institutions for the creation and dissemination of productive knowledge help explain the European advantage. We build a model of technological progress in a pre-industrial economy that emphasizes the person-to-person transmission of tacit knowledge. The young learn as apprentices from the old. Institutions such as the family, the clan, the guild, and the market organize who learns from whom. We argue that medieval European institutions such as guilds, and specific features such as journeymanship, can explain the rise of Europe relative to regions that relied on the transmission of knowledge within extended families or clans.
Keywords: E02; J24; N10; N30; O33; O43; 330; dissemination of knowledge; guilds; clans; apprenticeship